Door to Skin Time in Patients Undergoing Emergency Trauma Craniotomy - Chockalingam, Kumarappan (2020)
Background and Objective Traumatic brain injury (TBI) is predicted to be the third leading cause of death and disability worldwide in 20201. It places a significant burden on health care especially in developing countries like Malaysia. For a subset of patients’ with TBI with significant intracranial bleed, urgent surgical intervention remains the mainstay of treatment. Although all efforts are taken to ensure that patients received surgical intervention in a timely manner, often we find that there are inadvertent delays in management of these patients. This study aims to evaluate the performance of neurosurgery referral centre in Malaysia, review the possible pitfalls and propose ways to improve performance Methods This is a retrospective study conducted in HSAJB between 1st January 2019 and 31st December 2019. All patient with traumatic brain injury admitted to HSAJB with abnormal CT brain findings requiring urgent craniotomy was enrolled in this study. A list of patients who underwent emergency craniotomy or craniectomy from our operating theatre registry. The demographic data and required clinical data were extracted from the clinical notes. The data obtained were entered into computer software Statistical Package for Social Science (SPSS) version 22. Data distributions were described with nonparametric statistics. Results A total of 154 patients who were subjected to emergency trauma craniotomy during the duration of study was included in this study. Overall, the median Door to Skin times were 605 minutes, Door to CT time was 131 minutes, CT to Review time was 274 minutes, Review to Booking time was 20minutes, Booking to OT time was 90 minutes and OT to Skin time was 62 minutes. Patients who were directly admitted to HSAJB had an overall median Door to Skin time of 459 minutes. At discharge, there were a total of 102 patients (66.23%) with poor outcome. On performing simple logistic regression, we found that the polytrauma, hypotensive episode, ventilated patients, severe TBI and Door-Skin times were all significantly associated with poor outcomes. The adjusted OR for Door to Skin times was 1.005 with 95% CI (1.002-1.008). Hence, for every minute delay in Door to Skin time, there was 1.005 time increase likelihood of having poor outcome during discharge. During the 6 months follow up, the number of patients with poor outcome reduced to 58 patients (37.66%). We found that regardless of patients’ clinical characteristic, every minute delay in Door to Skin led to 1.008 (1.005 -1.011, CI 95%) times increase in having poor outcome at 6 months. Conclusion Door to Skin time is directly proportional to poor outcomes in patients with TBI. Despite being the regional neurosurgical and trauma referral centre, there are still significant delays in patient management leading to delayed surgical intervention. Concerted efforts from all parties involved in trauma care with established neurotrauma protocol are essential in eliminating this delay.